Examining the Neurophysiological Impact of Childhood Sexual Abuse in Men: A Series of fMRI Studies - Chiasson, Carley (Université d'Ottawa / University of Ottawa, 2021)
Childhood maltreatment can have detrimental consequences on individual well-being and cognitive functioning. One type of childhood maltreatment that remains stigmatized and under-researched among men is child sexual abuse (CSA). Research examining the neurophysiological consequences of CSA in males is limited even further. This dissertation presents three original research articles which provide preliminary evidence of the lasting neurophysiological impact of CSA in men. We recruited all male participants, of those who experienced CSA, some had PTSD (CSA+PTSD) others did not have PTSD (CSA-PTSD) allowing for the examination of differences in males with histories of CSA (but no PTSD) versus those who have CSA histories and PTSD. We also recruited control males with no CSA histories nor PTSD. Three functional MRI tasks and one resting state functional scan were obtained. The letter n-back, and an emotional picture n-back task were used in the first study as a measure of working memory and emotional processing. The first study highlights the lasting impact CSA can have on men, regarding brain activity during working memory, and working memory when negative emotional stimuli are involved. The second study examined how negative/traumatic memories are re-experienced. Results from the second study demonstrate that CSA impacts the neurophysiology of autobiographical memory for traumatic experiences. In the final study, resting state functional connectivity was examined within the default mode, salience and limbic networks, and differences in functional connectivity within the networks were observed. Together, these findings highlight the long-term neural impact of CSA and can validate the experience of men who have lived through CSA. They can also guide researchers and clinicians to potential avenues of support for the well-being of these men. These studies highlight the need for more research with men who have experienced CSA so we can fully understand their altered neurophysiological responses, and how this knowledge can be used to support their mental health and continued wellness throughout their lives.
Keywords: fMRI; Childhood sexual abuse; Working memory; Autobiographical memory; Resting state functional connectivity